2019
DOI: 10.20944/preprints201907.0120.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetics Theoretical Limits of Synthetic Genomes: The Cases of Artificials <em>Caulobacter </em>(<em>C. eth-2.0), Mycoplasma Mycoides (JCVI-Syn 1.0, JCVI-Syn 3.0 and JCVI_3A), E-coli and YEAST chr XII</em>

Abstract: In (Venetz et al., 2019), authors rebuilt the essential genome of Caulobacter crescentus through the process of chemical synthesis rewriting and studied the genetic information content at the level of its essential genes. Then, they reduced the native Caulobacter crescentus native Caulobacter NA1000 genome sequence real genome ( 4042929 bp ) to the 785,701-bp reduced synthetic genome. Here we demonstrate the existence of a palindromic-like mirror structure that exists in real genomes and disappears totally in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…More recently, we have shown that these same Fibonacci proportions of the genome of the mitochondria, the energy source of the human cell, are deteriorated by mutations associated with various cancers (perez, 2017). We also demonstrate how these same Fibonacci proportions of DNA make it possible to distinguish a genome of a real bacterium from its attempt at a synthetic chimera (Perez, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…More recently, we have shown that these same Fibonacci proportions of the genome of the mitochondria, the energy source of the human cell, are deteriorated by mutations associated with various cancers (perez, 2017). We also demonstrate how these same Fibonacci proportions of DNA make it possible to distinguish a genome of a real bacterium from its attempt at a synthetic chimera (Perez, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…« Thus, any codon radiates at long distance and vice versa ».The Master Code of this sequence then produces two signatures, one GENOMIC, the other for PROTEOMIC, materialized by 2 very strongly correlated curves. that is this level of coupling which will provide precious information on the COHESION or on the HETEROGENEITY [11] of this nucleotide sequence. in particular the extreme regions (mini / maxi) would be associated with biological functions such as active sites, chromosomes breakpoints, etc.…”
Section: Main Covid_19 Genes Involvedmentioning
confidence: 99%
“…Thirty years ago, after pioneering in A.I (Perez, 1988(Perez, , 1991, we published in a paper entitled "chaos, DNA, and neuro computers: the golden link" (Perez, 1991), presenting a numerical method to analyse dna sequences based on Fibonacci numbers . In 2017 (Perez, 1997(Perez, , 2017(Perez, , 2019, we revisited this method to démonstrate application of this method in mtDNA mutations involved on Human cancers. Fiftyeight years ago, (Montagnier L. § Kingsley Sanders F., 1963) Luc Montagnier described the isolation of an infectious double helix RNA in cells infected with a picornavirus.…”
Section: I-introductionmentioning
confidence: 99%